2009
DOI: 10.3390/s90402647
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Green Roof Environmental Monitoring and Meteorological Network in New York City

Abstract: Green roofs (with plant cover) are gaining attention in the United States as a versatile new environmental mitigation technology. Interest in data on the environmental performance of these systems is growing, particularly with respect to urban heat island mitigation and stormwater runoff control. We are deploying research stations on a diverse array of green roofs within the New York City area, affording a new opportunity to monitor urban environmental conditions at small scales. We show some green roof system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 7 publications
1
41
1
3
Order By: Relevance
“…Ref. [51]). The essential difference between an extensive and intensive roof is the type of vegetation and therefore the height of the vegetation layer.…”
Section: Vegetated Roofsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [51]). The essential difference between an extensive and intensive roof is the type of vegetation and therefore the height of the vegetation layer.…”
Section: Vegetated Roofsmentioning
confidence: 99%
“…The essential difference between an extensive and intensive roof is the type of vegetation and therefore the height of the vegetation layer. It can be assumed that extensive roofs generally have vegetation lower than 0.15 m and intensive roofs have vegetation higher than 0.15 m [51]. Intensive roofs have a larger effect on the heat flux through the roof since the amount of vegetation is higher.…”
Section: Vegetated Roofsmentioning
confidence: 99%
“…Additional studies using sensors have looked at how green spaces can have a positive influence on ambient environment, comfort, and improved air quality. Reported studies include Hangzhou (Shuo et al, 2010), New York City (Gaffin et al, 2009), and Tel Aviv (Cohen et al, 2010). While a wide variety of weather apps for smartphones already exist, user-centric weathermonitoring capabilities for smartphones have also started to emerge.…”
Section: Monitoring Ambient Weathermentioning
confidence: 99%
“…8 For new and re-roofing commercial projects, the market share of asphalt-based roofs has dropped from its historical dominance to about 35% [19]. Furthermore, a study by Urban & Roth [20] showed that a white single-ply membrane now costs the same as a black single-ply membrane.…”
Section: Sproul Et Al (Version Dated 11/01/2013)mentioning
confidence: 99%
“…Figure 4 of Gaffin et al [8] indicates that average July SR of an extensive green roof is 0.20. We assume that an aged white roof has an SR of 0.55, which can be rounded to three times the green roof SR owing to the uncertainty in both SR estimates.…”
mentioning
confidence: 99%